Selected Poems 1956–1988 by Thomas Shapcott - Merry, Bruce (LiNQ (Literature in North Queensland), 2016)
Bruce Merry reviews: Thomas Shapcott, Selected Poems 1956-1988, St Lucia, University of Queensland Press, 1989, 352 pp., $18.95.